The Effect of Regular Exercise on Some Respiratory Parameters in Amateur Footballers and Wrestlers - Bilici, Muhammed Fatih; Genç, Ayça (Uluslararası Bilim Kültür ve Spor Derneği (UBİKS), 2020)
[Abstract Not Available]
Keywords: Spor Hekimliği